2019
DOI: 10.1111/and.13486
|View full text |Cite
|
Sign up to set email alerts
|

Does varicocelectomy improve semen in men with azoospermia and clinically palpable varicocele?

Abstract: The effectiveness of varicocelectomy in nonobstructive azoospermia is controversial. The current study assessed the efficacy of microsurgical subinguinal varicocelectomy in nonobstructive azoospermic men with palpable varicocele and to evaluate predictive parameters of outcome. We reviewed the records of 723 patients who had microsurgical varicocelectomy and diagnostic testicular biopsy between 2012 and 2016 at a tertiary medical centre. Data pertaining to the physical, laboratory (semen analysis and hormonal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 56 publications
0
12
0
1
Order By: Relevance
“…All studies included participants that had a diagnosis of NOA and clinically significant varicoceles, although some studies confirmed varicocele presence with ultrasonography. The average sample size was 43 and mean (range) duration of follow-up was 10.5 (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22) months (Table 1 [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…All studies included participants that had a diagnosis of NOA and clinically significant varicoceles, although some studies confirmed varicocele presence with ultrasonography. The average sample size was 43 and mean (range) duration of follow-up was 10.5 (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22) months (Table 1 [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]).…”
Section: Resultsmentioning
confidence: 99%
“…A total of 13 of the studies assessed spermatogenesis after VR with an average rate of 27.3% [8][9][10][11][12][13][14][15][16][17][18][19][20]. For two of those studies, the sperm were specified to be motile [9,11].…”
Section: Presence Of Sperm In Postoperative Ejaculatementioning
confidence: 99%
See 1 more Smart Citation
“…Varicocele can negatively impact appropriate sperm production leading to decreased fertility and complete azoospermia in 4%‐14% of patients (Elbardisi et al., 2020). As spermatogenesis is under gonadotropic and androgenic control, the effects of hormonal changes in this system on treatment success in patients with varicocele‐related infertility have been a subject of curiosity.…”
Section: Discussionmentioning
confidence: 99%
“…1 Varicocele can negatively impact appropriate sperm production leading to decreased fertility and complete azoospermia in 4%−14% of patients. 2 The proposed detrimental effects of varicocele on testicular function include oxidative stress, high scrotal temperature with loss of the scrotal counter-cooling mechanism, reflux of adrenal metabolites, and changes in androgen production. 3 , 4 …”
Section: Introductionmentioning
confidence: 99%